Preparation method of high-catalysis long-durability titanium-based lead dioxide anode
By preparing TiN coating on the surface of the titanium substrate and loading RuO2, combining a multi-layer porous structure with dense and porous PbO2 layers, the existing titanium-based PbO2 anode has been solved, and high catalytic activity and long durability are achieved, and it is suitable for industrial difficult-to-degrade organic wastewater treatment.
Patent Information
- Application Number
- CN202411913504.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
AI Technical Summary
The existing titanium-based PbO2 anode has insufficient degradation activity and short service life in electrical oxidation engineering, making it difficult to meet the needs of difficult-to-degrade organic wastewater treatment in industrial areas.
By preparing a TiN coating on the surface of the titanium substrate and loading RuO2 on its surface to form a TiN/RuO2 composite intermediate layer, combining a multi-layer porous structure of dense and porous PbO2 layers, the catalytic activity and stability of the anode are improved.
High catalytic activity and long durability are achieved, the efficiency of removing organic pollutants is significantly improved, and the service life of the anode is extended.
Smart Images

Figure CN119736628A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical engineering functional material development, and particularly relates to a method for preparing a high-catalytically active and long-durable titanium-based PbO2 anode. Background Art
[0002] Electrochemical oxidation technology uses the anode surface to convert water molecules into HO˙ and other strong oxidizing active oxygen species for mediated oxidation, or / and direct oxidation of organic pollutants to achieve efficient degradation of difficult-to-degrade pollutants. It has the advantages of simple operation, high degradation efficiency, low cost, and no secondary pollution. It is an electrochemical water treatment technology with great development and engineering application promotion. Among various technical factors, the anode material determines the mechanism of electron transfer in the electrochemical reaction, has a huge impact on the generation of strong oxidizing substances, and is considered to be the most important factor. As far as the various types of inactive anode materials currently developed are concerned, compared with boron-doped diamond (BDD), titanium oxide (Ti4O7) and other anodes, lead dioxide (PbO2) titanium-based shape-stable anode stands out because of its excellent comprehensive properties such as obvious economy, high HO˙ generation rate, electrodeposition production and relatively high stability. Even though it is considered to have a potential risk of lead ion leakage toxicity, it is still considered to be the most suitable economic electrode material for the treatment of industrial difficult-to-degrade organic wastewater. However, the PbO2 titanium anodes prepared by current technology generally expose prominent problems such as the need to improve degradation activity and short service life in the promotion of electro-oxidation projects. Summary of the invention
[0003] In order to overcome the defects of the above-mentioned Ti / PbO2 anode material, the present invention aims to provide a method for preparing a titanium-based PbO2 anode with high catalytic activity and long durability, so as to prepare a titanium-based PbO2 electrode material with high catalytic activity and long life.
[0004] Based on the invention of the shape-stable anode by Bell, the widespread industrial application of chlor-alkali and a large number of continuous and in-depth studies, a consensus has gradually been formed: the improvement and regulation of the titanium substrate, the introduced intermediate layer and the surface PbO2 catalyst layer (i.e., the three structural components) can obtain electrodes with different structural compositions, which can give it corresponding functions and characteristics. A large number of research results have confirmed that the introduction of a suitable intermediate layer can significantly extend the service life of the anode and may also take into account the enhancement of electrocatalytic activity to a certain extent. According to previous research findings of our research group, the introduction of arc-sprayed TiN intermediate layer can greatly improve the stability of titanium-based PbO2 anodes and promote the improvement of catalytic activity, but it still cannot achieve the significant life extension effect of the introduction of the precious metal oxide IrO2-Ta2O5 intermediate layer. Considering that the oxides of precious metals Ir and Ta significantly enhance the stability of PbO2 anodes, in addition to helping to increase the bonding strength, it should also rely on their contribution to the "oxygen barrier" catalytic effect of inhibiting the diffusion and penetration of active oxygen [O] into the substrate during the oxidation process. Therefore, it is proposed to modify the surface of arc-sprayed TiN intermediate layer with different contents of RuO2 to achieve both strong bonding and "oxygen barrier" catalytic effect to improve the service life of titanium-based PbO2 anode. For the surface PbO2 catalytic layer, the use of porous structure has been considered to be a necessary feature of the ideal electrode. The porous structure of the anode often has the advantages of high activity, high limiting current density, short-path efficient oxidation, etc. However, the direct electrodeposition of porous PbO2 layer used in previous studies, although it enhances the catalytic oxidation activity of the anode, will significantly deteriorate the anode life due to the weakening of the porous PbO2's barrier effect on the medium and the new oxygen penetration erosion; at the same time, the PbO2 deposition layer often reduces the fracture toughness due to the porosity, and the cohesive bonding of the coating itself or the bonding strength between the coatings is reduced, which makes the electrodeposition difficult to maintain for a long time. Therefore, the deposition thickness of the porous PbO2 surface layer is limited, and a thick coating cannot be obtained. Inspired by the multilayer film structure, it is now proposed to use a dense layer and a porous layer to deposit a multilayer porous structure surface PbO2 coating. The TiN / RuO2 composite intermediate layer is obtained by arc spraying TiN + pyrolysis of RuO2, and the dense layer and the porous layer are jointly deposited to obtain a multi-layer porous structure PbO2 surface coating, thereby realizing the preparation of high-performance titanium-based PbO2 anode. This method has obvious technical advantages of being operationally feasible and having both good performance.
[0005] Based on this, the technical solution adopted by the present invention is:
[0006] A method for preparing a titanium-based PbO2 anode with high catalytic activity and long durability comprises the following steps:
[0007] Step 1, preparing a TiN coating on the surface of a pretreated titanium substrate using arc spraying technology;
[0008] Step 2, brushing and thermally decomposing a small amount of precious metal oxide RuO2 on the surface of the arc sprayed TiN coating to obtain a TiN / RuO2 composite intermediate layer;
[0009] Step 3, on the surface of the TiN / RuO2 composite intermediate layer, first electrodeposit a dense PbO2 sublayer, then use the oxygen bubble template method to electrodeposit a porous PbO2 sublayer, and then alternately deposit the two for multiple cycles to prepare a PbO2 surface layer with a multi-layer porous structure, and finally obtain a Ti / TiN / RuO2 / P-PbO2 anode, wherein P represents the multi-layer porous structure of the electrode.
[0010] The spraying in step 1 is to pass two continuously supplied Ti wires through an arc spraying device under an atmospheric environment. Under the action of a high-temperature arc, the tip of the conveyed wire is instantly heated and melted, and a molten jet is formed, which impacts the surface to be coated at a certain rate; at the same time, the molten jet contacts and reacts with nitrogen in the air, and a TiN coating is finally formed as the molten droplets cool. The spraying power is set to 30-40kW, the working voltage is 8-15V, the spraying distance is controlled to 50-150mm, and the diameter of the Ti wire is 1.5-2.0mm. The thickness of the TiN coating is controlled to 200-400μm.
[0011] In the step 2, a ruthenium salt solution of a certain concentration is dipped with a brush, and then the surface of the TiN sprayed layer is coated multiple times. The present invention selects to coat the titanium sample surface sprayed with the TiN coating three times, and more typically, it can be coated manually. After each coating is completed, it is first dried in an oven at 100-200°C for 5-10 minutes, and then the next brush coating is performed. After multiple coatings are completed, it is sintered in a muffle furnace at 420-470°C for 1-2 hours to pyrolyze to generate RuO2, and finally a TiN / RuO2 composite intermediate layer loaded with RuO2 is obtained. The present invention can control the loading amount of RuO2 to be 1-3 mg / cm 2 .
[0012] The ruthenium salt solution is a ruthenium salt solution with a concentration of 0.1 M formed by dissolving RuCl3·H2O in a 20% HCl aqueous solution.
[0013] In step 3, the TiN / RuO2 composite intermediate layer is used as an anode, and a stainless steel plate of the same size as the anode is used as a cathode. In an electrodeposition solution containing or only containing Pb(NO3)2, HNO3 and [Emim]BF4 (1-ethyl-3-methyl-imidazolium tetrafluoroborate) ionic liquid, a dense PbO2 sublayer is electrodeposited on the TiN / RuO2 composite intermediate layer to obtain a dense PbO2 sublayer on the TiN / RuO2 composite intermediate layer; during the process, the current density is controlled at 20-40 mA / cm 2, temperature 60-80°C. Then, the porous PbO2 sublayer is anodic electrodeposited on the dense PbO2 sublayer, with the workpiece with the dense PbO2 sublayer electrodeposited as the anode and the stainless steel plate of the same size as the cathode, and the anodic electrodeposition current density is controlled to be 100-200mA / cm 2 Anodic electrodeposition is carried out in a deposition solution containing 0.2-0.6 mol / L Pb(NO3)2, 0.1-0.2 mol / L HNO3, 0.1-0.3 mol / LCH3COONa·3H2O, 0.03-0.06 mol / L Cu(NO3)2·3H2O and 0.01-0.03 g / L sodium dodecylbenzene sulfonate (SDBS) at a temperature of 50-80°C to obtain a porous PbO2 sublayer on the dense PbO2 sublayer.
[0014] The multi-layer porous structure of the PbO2 coating is obtained by depositing dense PbO2 sublayers and porous PbO2 sublayers in sequence for multiple cycles. The fixed bottom of the PbO2 catalytic surface is always a dense PbO2 sublayer, and the outer surface is always a porous PbO2 sublayer. Each cycle is always composed of a dense PbO2 sublayer and a porous PbO2 sublayer thereon. The number of cycles of the multi-cycle sequential deposition of the multi-layer porous structure of the PbO2 catalytic surface does not exceed 4, and the total thickness of the PbO2 catalytic surface is controlled to be 300-500μm. After the deposition is completed, the anode is rinsed with distilled water and dried in an oven at 60°C to obtain a multi-layer porous PbO2 titanium anode.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. The present invention loads a small amount of RuO2 on the surface of the TiN coating prepared by arc spraying technology to obtain a TiN / RuO2 composite intermediate layer. The arc spraying method is convenient to prepare and has high efficiency. When a solid coating is formed, due to high temperature and high-speed collision, part of the material will splash and then form droplet-shaped particles. The presence of solid particles makes the surface of the intermediate layer coarsened, which not only helps to load RuO2 and form a composite intermediate layer, but also increases the riveting between the surface PbO2 layer and the intermediate layer, thereby obtaining a higher bonding strength, which helps to enhance the stability of the electrode.
[0017] 2. The present invention utilizes the periodic alternating deposition of dense PbO2 sublayers and porous PbO2 sublayers to obtain a thicker multilayer PbO2 coating, which not only improves the electrode catalytic activity, but also overcomes the problem that the electrodeposition of a simple porous PbO2 coating cannot be maintained due to the inherent low bonding strength and low fracture toughness of the skeleton. The dense lower sublayer should play an important bonding role, and the multilayer structure has a certain toughening effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1Surface SEM images and corresponding cross-sectional SEM images of the Ti / TiN / RuO2 / P-PbO2-1 electrode, Ti / TiN / RuO2 / P-PbO2-2 electrode, Ti / TiN / RuO2 / P-PbO2-3 electrode, Ti / TiN / RuO2 / P-PbO2-4 electrode, Ti / TiN / RuO2 / PbO2 electrode and Ti / PbO2 comparison electrode prepared by the present invention.
[0019] Figure 2 This is the XRD diagram of the Ti / TiN / RuO2 composite intermediate layer prepared in the present invention.
[0020] Figure 3 CV diagrams of the Ti / TiN / RuO2 / P-PbO2-1 electrode, Ti / TiN / RuO2 / P-PbO2-2 electrode, Ti / TiN / RuO2 / P-PbO2-3 electrode, Ti / TiN / RuO2 / P-PbO2-4 electrode, Ti / TiN / RuO2 / PbO2 electrode and Ti / PbO2 comparison electrode prepared by the present invention.
[0021] Figure 4 EIS graphs of the Ti / TiN / RuO2 / P-PbO2-1 electrode, Ti / TiN / RuO2 / P-PbO2-2 electrode, Ti / TiN / RuO2 / P-PbO2-3 electrode, Ti / TiN / RuO2 / P-PbO2-4 electrode, Ti / TiN / RuO2 / PbO2 electrode and Ti / PbO2 comparison electrode prepared by the present invention.
[0022] Figure 5 The accelerated life and norfloxacin removal efficiency comparison diagram of the Ti / TiN / RuO2 / P-PbO2-1 electrode, Ti / TiN / RuO2 / P-PbO2-2 electrode, Ti / TiN / RuO2 / P-PbO2-3 electrode, Ti / TiN / RuO2 / P-PbO2-4 electrode and Ti / TiN / RuO2 / PbO2 electrode and Ti / PbO2 comparison electrode prepared by the present invention. DETAILED DESCRIPTION
[0023] The embodiments of the present invention are described in detail below with reference to the accompanying drawings and examples.
[0024] The present invention is a method for preparing a titanium-based PbO2 anode with high catalytic activity and long durability. The method comprises the following steps: firstly obtaining a TiN coating on the surface of a pretreated titanium substrate by arc spraying technology, and then loading a small amount of precious metal oxide RuO2 on the surface by brushing to prepare a TiN / RuO2 composite intermediate layer; then firstly depositing a dense PbO2 sublayer thereon, and then depositing a porous PbO2 sublayer by an oxygen bubble template method, and then periodically and repeatedly co-depositing the two to prepare a PbO2 surface catalytic layer with a multi-layer porous structure, and finally preparing a Ti / TiN / RuO2 / P-PbO2 anode with high catalytic activity and long durability service characteristics, which is composed of a TiN / RuO2 composite intermediate layer + a multi-layer porous PbO2 surface layer. The anode has high catalytic activity and long durability, and has a significant removal effect on organic pollutant wastewater.
[0025] Specifically, the preparation method of the present invention mainly comprises the following three steps:
[0026] Step 1, using arc spraying technology to prepare a conductive TiN coating on the surface of a pretreated titanium substrate;
[0027] Step 2, thermally decomposing and loading a small amount of precious metal oxide RuO2 on the surface of the arc sprayed TiN coating to obtain a TiN / RuO2 composite intermediate layer;
[0028] Step 3, on the RuO2-modified TiN / RuO2 composite intermediate layer, first electrodeposit a dense PbO2 sublayer, and then use the oxygen bubble template method to electrodeposit a porous PbO2 sublayer, and alternately perform co-deposition of the two for different numbers of cycles to ultimately prepare a Ti / TiN / RuO2 / P-PbO2-X anode with a multilayer porous structure, wherein P represents the multilayer porous structure of the electrode, and X represents the number of cycles of co-deposition to obtain the PbO2 active layer.
[0029] The present invention optimizes the number of cycles of co-deposition of dense PbO2 sublayers and porous PbO2 sublayers to prepare a multilayer porous PbO2 titanium anode with high catalytic activity and long durability containing a TiN / RuO2 composite intermediate layer. The method is easy to operate, and the prepared anode has the advantages of high catalytic activity, high limiting current density, short-path efficient oxidation and long service life. It can promote the development of high-performance PbO2 anodes, and also provide technical support for the application of electro-oxidation technology in repairing difficult-to-degrade pollution projects.
[0030] In the embodiment of the present invention, the pretreatment of the titanium plate mainly includes sodium hydroxide alkaline washing to remove oil, oxalic acid etching and surface sandblasting, the purpose of which is to obtain a rough surface without oil stains and oxide layer.
[0031] Step 1 of the present invention utilizes arc spraying equipment to spray in an atmospheric environment, and two continuously supplied titanium wires are simultaneously sent to the center of the nozzle through a conductive nozzle, and are used as the positive electrode and negative electrode of the consumable electrode respectively. When the distance between the two electrodes reaches a critical distance, an arc is triggered; due to the high temperature characteristics of the arc, the tip of the conveyed wire is instantly heated and melted, and a molten jet is formed, which impacts the surface to be coated at a certain rate; at the same time, the molten jet contacts and reacts with nitrogen in the air, and as the molten droplets cool, they finally condense to form a TiN coating. It belongs to a ceramic material, has stable chemical properties, has certain conductivity, and has high corrosion resistance, hardness and strength, and structural adhesion.
[0032] A feasible process parameter is:
[0033] The wire diameter is 1.5-2.0mm, the arc spraying power is set to 30-40kW, the working voltage is 8-15V, and the spraying distance is controlled to 50-150mm.
[0034] In step 2 of the present invention, a ruthenium salt solution of a certain concentration is dipped with a brush, and then the titanium sample sprayed with the TiN coating is manually coated multiple times. After each coating is completed, it is first dried in an oven at 100-200°C for 5-10 minutes, and then sintered in a muffle furnace at 420-470°C for 1-2 hours to pyrolyze RuO2, and finally a TiN / RuO2 composite intermediate layer loaded with RuO2 is obtained.
[0035] A feasible process parameter is:
[0036] The composition of the ruthenium salt solution is: RuCl3·H2O is dissolved in a 20% HCl aqueous solution to form a ruthenium salt solution with a concentration of 0.1M.
[0037] Step 3 of the present invention is to first use the TiN / RuO2 composite intermediate layer as an anode and a stainless steel plate of the same size as a cathode to perform anodic electrodeposition in an electrodeposition solution containing or only containing Pb(NO3)2, HNO3 and 1-ethyl-3-methyl-imidazolium tetrafluoroborate ionic liquid to obtain a dense PbO2 sublayer on the TiN / RuO2 composite intermediate layer. Then, the dense PbO2 sublayer electrodeposited on the TiN / RuO2 composite intermediate layer is used as an anode and the stainless steel plate of the same size is used as a cathode to perform anodic electrodeposition in an electrodeposition solution containing or only containing Pb(NO3)2, HNO3, CH3COONa·3H2O, Cu(NO3)2·3H2O and sodium dodecylbenzene sulfonate (SDBS) to obtain a porous PbO2 sublayer on the dense PbO2 sublayer. Then, the dense PbO2 sublayer and the porous PbO2 sublayer were alternately co-deposited for different number of cycles, and finally a Ti / TiN / RuO2 / P-PbO2-X anode with a multi-layer porous structure was prepared, where P represents the multi-layer porous structure of the electrode, and X represents the number of cycles of co-deposition to obtain the PbO2 active layer. During the co-deposition process of different cycles, the total deposition time was guaranteed to be 120 minutes, and the deposition time of each cycle (dense sublayer + porous sublayer) was evenly distributed; among them, the deposition time of the porous sublayer in each cycle was fixed at 10 minutes, and the remaining time was the deposition time of the dense sublayer.
[0038] A feasible process parameter is:
[0039] The dense PbO2 sublayer electrodeposition solution consists of 0.2-0.4 mol / L Pb(NO3)2, 0.1-0.3 mol / L HNO3 and 30-50 mg / L [Emim] BF4 (1-ethyl-3-methyl-imidazolium tetrafluoroborate), and the anodic electrodeposition current density is 20-40 mA / cm 2 , water bath temperature 60-80℃, electrodeposition time 30min. The composition of the porous PbO2 sublayer electrodeposition solution is 0.2-0.6mol / L Pb(NO3)2, 0.1-0.2mol / L HNO3, 0.1-0.3mol / L CH3COONa·3H2O, 0.03-0.06mol / L Cu(NO3)2·3H2O and 0.01-0.03g / L sodium dodecylbenzene sulfonate (SDBS), and the anodic electrodeposition current density is 100-200mA / cm 2 , temperature 50-80°C, electrodeposition time 10 min. Three cycles of combined deposition were performed alternately.
[0040] After the deposition is completed, the anode is rinsed with distilled water and dried in an oven at 60° C. to obtain a multilayer porous PbO2 titanium anode containing a TiN / RuO2 composite intermediate layer.
[0041] Three specific embodiments of the present invention are as follows.
[0042] Example 1
[0043] A method for preparing a titanium-based PbO2 anode with high catalytic activity and long durability, firstly, the polished titanium plate is subjected to sodium hydroxide alkaline washing and oil removal, oxalic acid etching and surface sandblasting treatment to obtain a rough surface without oil stains and oxide layer. Then, in an atmospheric environment, two continuously supplied titanium wires are simultaneously sent to the center of the nozzle through a conductive nozzle using an arc spraying device, and are used as the positive electrode and negative electrode of the consumable electrode respectively. When the distance between the two electrodes reaches a critical distance, an arc is triggered; due to the high temperature characteristics of the arc, the tip of the conveyed wire is instantly heated and melted, and a molten jet is formed, which impacts the surface to be coated at a certain rate; at the same time, the molten jet will contact and react with nitrogen in the air, and as the molten droplets cool, they will eventually condense to form a TiN coating. Then, a brush was dipped into a 0.1M ruthenium salt solution to manually coat the titanium sample sprayed with TiN coating. After coating, it was first dried in a 150℃ oven for 5 minutes, and then sintered in a 450℃ muffle furnace for 1 hour to pyrolyze RuO2 to obtain a TiN / RuO2 composite interlayer loaded with RuO2. Then, the titanium-based TiN / RuO2 composite interlayer was used as the anode and a stainless steel plate of the same size was used as the cathode. Anode electrodeposition was performed in an electrodeposition solution containing or only containing Pb(NO3)2, HNO3 and 1-ethyl-3-methyl-imidazolium tetrafluoroborate ionic liquid to obtain a dense PbO2 sublayer. Then, the anode is used as the anode and the stainless steel plate of the same size is used as the cathode. Anode electrodeposition is carried out in an electrodeposition solution containing or only containing Pb(NO3)2, HNO3, CH3COONa·3H2O, Cu(NO3)2·3H2O and sodium dodecylbenzene sulfonate (SDBS), and a porous PbO2 sublayer is obtained on the dense PbO2 sublayer. Finally, the dense PbO2 sublayer and the porous PbO2 sublayer are alternately co-deposited for three cycles to obtain a multilayer porous Ti / TiN / RuO2 / P-PbO2-3 anode with a TiN / RuO2 composite intermediate layer.
[0044] For comparison, based on the same steps mentioned above, the dense PbO2 sublayer and the porous PbO2 sublayer were also co-deposited for 1 cycle, 2 cycles and 4 cycles, respectively, to obtain the Ti / TiN / RuO2 / P-PbO2-1 anode, Ti / TiN / RuO2 / P-PbO2-2 anode and Ti / TiN / RuO2 / P-PbO2-4 anode, respectively.
[0045] Process parameters in this example: diameter of titanium wire for TiN coating: 1.6 mm; spray preheating temperature: 80°C; spray working voltage: 10 V; spray power: 36 kW; spray distance: 100 mm; current density for electrodeposition of dense PbO2 sublayer: 30 mA / cm2 , the temperature is 60℃; the current density of the porous PbO2 sublayer electrodeposition is 150mA / cm 2 , the temperature is 60℃. During the three-cycle combined deposition, the deposition time of the dense PbO2 sublayer is 30min, and the deposition time of the porous PbO2 sublayer is 10min; during the one-cycle combined deposition, the deposition time of the dense PbO2 sublayer is 110min, and the deposition time of the porous PbO2 sublayer is 10min; during the two-cycle combined deposition, the deposition time of the dense PbO2 sublayer is 50min, and the deposition time of the porous PbO2 sublayer is 10min. During the four-cycle combined deposition, the deposition time of the dense PbO2 sublayer is 20min, and the deposition time of the porous PbO2 sublayer is 10min.
[0046] Taking norfloxacin as the target pollutant, a 200 mg / L norfloxacin solution was prepared. At a current density of 20 mA / cm 2 Under the conditions of temperature of 20℃ and pH=3, with Ti / TiN / RuO2 / P-PbO2-3 as the anode and the stainless steel plate of the same size as the cathode, the degradation rate of norfloxacin reached 87.68% after 3h of electrolysis; with Ti / TiN / RuO2 / P-PbO2-1 as the anode, the degradation rate of norfloxacin reached 84.81% after 3h of electrolysis; with Ti / TiN / RuO2 / P-PbO2-2 as the anode, the degradation rate of norfloxacin reached 81.69% after 3h of electrolysis; with Ti / TiN / RuO2 / P-PbO2-4 as the anode, the degradation rate of norfloxacin reached 84.07% after 3h of electrolysis.
[0047] Example 2
[0048] A method for preparing a titanium-based PbO2 anode with high catalytic activity and long durability, firstly, the polished titanium plate is subjected to sodium hydroxide alkaline washing and oil removal, oxalic acid etching and surface sandblasting treatment to obtain a rough surface without oil stains and oxide layer. Then, in an atmospheric environment, two continuously supplied titanium wires are simultaneously sent to the center of the nozzle through a conductive nozzle using an arc spraying device, and are used as the positive electrode and negative electrode of the consumable electrode respectively. When the distance between the two electrodes reaches a critical distance, an arc is triggered; due to the high temperature characteristics of the arc, the tip of the conveyed wire is instantly heated and melted, and a molten jet is formed, which impacts the surface to be coated at a certain rate; at the same time, the molten jet will contact and react with nitrogen in the air, and as the molten droplets cool, they will eventually condense to form a TiN coating. Then, a brush was dipped into a 0.1M ruthenium salt solution to manually coat the titanium sample sprayed with TiN coating. After coating, it was first dried in a 150℃ oven for 5 minutes, and then sintered in a 450℃ muffle furnace for 1 hour to pyrolyze RuO2 to obtain a TiN / RuO2 composite interlayer loaded with RuO2. Then, the titanium-based TiN / RuO2 composite interlayer was used as the anode and a stainless steel plate of the same size was used as the cathode. Anode electrodeposition was performed in an electrodeposition solution containing or only containing Pb(NO3)2, HNO3 and 1-ethyl-3-methyl-imidazolium tetrafluoroborate ionic liquid to obtain a Ti / TiN / RuO2 / PbO2 anode.
[0049] The process parameters in this example are: diameter of titanium wire of TiN coating: 1.6mm; spray preheating temperature: 80℃; spray working voltage: 10V; spray power: 36kW; spray distance: 100mm; electrodeposition time: 120min, current density: 30mA / cm 2 , temperature 60℃.
[0050] Taking norfloxacin as the target pollutant, a 200 mg / L norfloxacin solution was prepared. At a current density of 20 mA / cm 2 Under the conditions of temperature of 20℃ and pH=3, with Ti / TiN / RuO2 / PbO2 as anode and stainless steel plate of the same size as cathode, the degradation rate of norfloxacin reached 72.67% after 3h of electrolysis.
[0051] Example 3
[0052] A method for preparing a conventional Ti / PbO2 electrode comprises the following steps: firstly, the polished titanium plate is subjected to sodium hydroxide alkaline washing for oil removal, oxalic acid etching and surface sandblasting to obtain a rough surface without oil stains and oxide layer. Then, Ti / PbO2 is used as an anode and a stainless steel plate of the same area is used as a cathode, and electroplating is performed for 120 minutes in a deposition solution containing Pb(NO3)2, HNO3 and 1-ethyl-3-methyl-imidazolium tetrafluoroborate ionic liquid to obtain a Ti / PbO2-2.0 electrode.
[0053] The process parameters in this example are: electrodeposition time is 120 min, current density is 30 mA / cm 2 , temperature 60℃.
[0054] Taking norfloxacin as the target pollutant, a 200 mg / L norfloxacin solution was prepared. At a current density of 20 mA / cm 2 Under the conditions of temperature of 20℃ and pH=3, with Ti / TiN / RuO2 / P-PbO2-2 as the anode and a stainless steel plate of the same size as the cathode, the degradation rate of norfloxacin reached 67.30% after 3 hours of electrolysis.
[0055] Figure 1 af and a′-f′ are surface SEM images of Ti / PbO2, Ti / TiN / RuO2 / PbO2 (comparative electrode) and different multilayer porous Ti / TiN / RuO2 / P-PbO2-X (X=1-4) electrodes prepared by the present invention. It can be seen from the figure that the minimum current density is 30mA / cm 2 After depositing PbO2, the anode surface presents the typical morphological features of flat and dense PbO2, with a compact structure and a typical "pyramid" feature. It is obviously different from the Ti / TiN / RuO2 / P-PbO2-X electrodes with different periodic surfaces, whose surfaces all have a clearly recognizable "porous" structure, and the pore walls are made up of many interconnected PbO2 particles. Comparing the effects of different cycles, it can be seen that the particle clusters on the surface of the porous PbO2 electrode formed by single-cycle alternating deposition are relatively dense, and the mutual accumulation is more serious. The holes formed by the overflow of oxygen bubbles are relatively few. With the increase in the number of deposition cycles, the particle clusters on the electrode surface appear looser and the particle size is more uniform, which will help to obtain a larger specific surface area and provide more active sites for electro-oxidative degradation. However, after 4 cycles of alternating deposition, the PbO2 grain clusters on the electrode surface are seriously accumulated.
[0056] Figure 1gk are cross-sectional SEM images of the Ti / TiN / RuO2 / PbO2 electrode and different multi-layer porous Ti / TiN / RuO2 / P-PbO2-X (X=1-4) electrodes prepared by the present invention. It can be seen from the cross-sectional image that the thickness of RuO2 cannot be distinguished from the cross-sectional image due to too little loading. On the TiN / RuO2 composite intermediate layer, the thicker multi-layer PbO2 coating is obtained by periodically alternating the deposition of dense PbO2 sublayers and porous PbO2 sublayers, which overcomes the problem that the electrodeposition of the simple porous PbO2 coating cannot be maintained due to the inherent low bonding strength and low fracture toughness of the skeleton. The dense lower sublayer should play an important bonding role, and the multi-layer structure has a certain toughening effect. According to the porous sublayer profile of Ti / TiN / RuO2 / P-PbO2-1 electrode and the pore distribution and morphology of the porous layer deposited in the first cycle of Ti / TiN / RuO2 / P-PbO2-3 electrode, it can be found that the pores formed by delayed overflow of oxygen bubbles have obvious randomness and do not have regular distribution characteristics and morphology. Moreover, the thickness of each periodic deposition layer obtained from the dense PbO2 sublayer and the porous PbO2 sublayer shows a slight increasing trend (from about 180μm to nearly 250μm), which will help to extend the service life of the electrode.
[0057] Figure 2 From the surface XRD pattern of the Ti / TiN / RuO2 composite interlayer prepared in the present invention, it is not difficult to see that the surface of the TiN / RuO2 composite interlayer is composed of two phases, TiN and Ti3O, indicating that during the arc spraying process, the molten Ti reacts with the nitrogen in the air to form TiN by nitridation, and a small amount of Ti3O is caused by oxidation of the formed TiN under the action of high temperature in the subsequent preparation; no characteristic peak related to RuO2 is found, which is due to the small loading amount of RuO2.
[0058] Figure 3 The CV graphs of different multilayer porous Ti / TiN / RuO2 / P-PbO2-X (X=1-4) electrodes and Ti / TiN / RuO2 / PbO2 electrodes and Ti / PbO2 comparison electrodes prepared by the present invention show that the introduction of the TiN / RuO2 composite intermediate layer and the porous structure of the electrode surface both increase the peak current of the electrode sharply, and the closed area of the CV curve increases, that is, the amount of charge generated by the electrode reaction increases, thereby suggesting that the electrochemical active surface area / number of active sites of the electrode increases. The Ti / TiN / RuO2 / P-PbO2-3 electrode has the largest CV area and the highest peak current.
[0059] Figure 4From the EIS graphs of different multilayer porous Ti / TiN / RuO2 / P-PbO2-X (X=1-4) electrodes, Ti / TiN / RuO2 / PbO2 electrodes and Ti / PbO2 comparison electrodes prepared by the present invention, it can be seen that the TiN / RuO2 composite intermediate layer causes the capacitive arc radius of the PbO2 anode to decrease, and the corresponding charge transfer resistance Rct becomes smaller; the capacitive arc of the multilayer porous structure Ti / TiN / RuO2 / P-PbO2-X electrode is reduced again, and the charge transfer resistance R ct become smaller, which means that the electrocatalytic activity of the electrode increases. The R ct The minimum value indicates that the electrochemical reaction rate of the electrode in the solution becomes faster, and it has good conductivity and electrocatalytic activity.
[0060] Figure 5The accelerated life and removal rate of norfloxacin of different multilayer porous Ti / TiN / RuO2 / P-PbO2-X (X=1-4) electrodes, Ti / TiN / RuO2 / PbO2 electrodes and Ti / PbO2 comparison electrodes prepared by the present invention are compared. It can be seen that compared with the Ti / PbO2 electrode (33.5h), the accelerated life of the electrode is significantly increased (extended by about 15 times) after the introduction of the TiN / RuO2 composite intermediate layer; the accelerated life of the electrode of the three-component structure of "titanium substrate / TiN / RuO2 composite intermediate layer / surface multilayer porous PbO2 layer" designed and constructed is reduced due to the introduction of the porous structure of the surface PbO2, but compared with the Ti / PbO2 electrode, it has a longer accelerated life. The multilayer porous Ti / TiN / RuO2 / P-PbO2-X electrode prepared by the present invention can obtain good durability while taking into account high catalytic activity. This is due to the presence of arc sprayed TiN, which makes the matrix and the surface layer have a stronger bonding force, and improves the anti-stripping ability of the anode surface; and RuO2 is a material with catalytic activity and oxygen evolution function. After a period of accelerated life test, the active oxygen in the electrolyte penetrates into the middle layer through the cracks. Since the TiN / RuO2 middle layer can discharge the active oxygen into the electrolyte through the surface holes before it is converted into oxygen bubbles, it effectively prevents the oxygen bubbles from scouring the anode surface. The combination of the two contributes to its long life. In addition, the above six electrodes have a norfloxacin removal rate of 84.81%, 81.69%, 87.68%, 84.07%, 72.67% and 67.30% respectively. It can be seen that the Ti / TiN / RuO2 / P-PbO2-3 electrode prepared in the embodiment of the present invention has the highest norfloxacin removal rate because it has the largest electrochemical active surface area. In addition, the Ti / TiN / RuO2 / P-PbO2-X electrode prepared by the present invention has a relatively long service life, which indicates that the electrode prepared by the method of the present invention is more suitable for treating wastewater containing difficult-to-degrade organic pollutants.
[0061] The above is a detailed introduction to the preparation method of a titanium-based PbO2 anode with high catalytic activity and long durability of the present invention. Specific examples show that the multilayer porous Ti / TiN / RuO2 / P-PbO2-3 electrode with a TiN / RuO2 composite intermediate layer has significant improvements in both catalytic activity and service life compared to traditional Ti / PbO2 electrodes. Among them, the introduction of the TiN / RuO2 composite intermediate layer greatly prolongs the service life of traditional Ti / PbO2 electrodes, and the porosity of the surface PbO2 greatly improves the catalytic activity of traditional Ti / PbO2 electrodes. This specification provides a certain reference value for the high-efficiency and long-service life treatment of wastewater with difficult-to-degrade organic pollutants.
Claims
1. A method for preparing a highly catalytic and long-lasting titanium-based lead dioxide anode, characterized in that: The steps include: Step 1, preparing a TiN coating on the surface of a pretreated titanium substrate using arc spraying technology; Step 2, brushing and thermally decomposing the precious metal oxide RuO2 on the surface of the arc sprayed TiN coating to obtain a TiN / RuO2 composite intermediate layer; Step 3, on the surface of the TiN / RuO2 composite intermediate layer, first electrodeposit a dense PbO2 sublayer, then use the oxygen bubble template method to electrodeposit a porous PbO2 sublayer, and then alternately deposit the two for multiple cycles to prepare a PbO2 catalytic surface layer with a multi-layer porous structure, and finally obtain a Ti / TiN / RuO2 / P-PbO2 anode, wherein P represents the multi-layer porous structure of the electrode.
2. The method for preparing a highly catalytic and long-lasting titanium-based lead dioxide anode according to claim 1, characterized in that: The thickness of the TiN coating and the TiN / RuO2 composite intermediate layer are both controlled to be 200-400 μm, and the total thickness of the PbO2 catalytic surface layer with a multi-layer porous structure is controlled to be 300-500 μm.
3. The method for preparing a highly catalytic and long-durable titanium-based lead dioxide anode according to claim 1 or 2, characterized in that: The spraying in step 1 is carried out in an atmospheric environment by arc spraying using two continuously supplied Ti wires, the molten jet contacts and reacts with nitrogen in the air, and a TiN coating is finally formed as the molten droplets cool; wherein the spraying power is set to 30-40kW, the operating voltage is 8-15V, the spraying distance is controlled to 50-150mm, and the diameter of the Ti wire is 1.5-2.0mm.
4. The method for preparing a highly catalytic and long-durable titanium-based lead dioxide anode according to claim 1 or 2, characterized in that: In the step 2, a ruthenium salt solution is dipped into a brush, and then the surface of the TiN spray layer is coated multiple times. After each coating is completed, it is first dried in an oven at 100-200°C for 5-10 minutes, and then the next coating is performed; after multiple coatings are completed, it is selected to be sintered in a muffle furnace at 420-470°C for 1-2 hours to pyrolyze and generate RuO2; finally, a TiN / RuO2 composite intermediate layer is obtained.
5. The method for preparing a highly catalytic and long-lasting titanium-based lead dioxide anode according to claim 4, characterized in that: The surface of the titanium sample sprayed with TiN coating was coated three times, and the loading amount of RuO2 was controlled to be 1-3 mg / cm 2 .
6. The method for preparing a highly catalytic and long-lasting titanium-based lead dioxide anode according to claim 4, characterized in that: The ruthenium salt solution is prepared by dissolving RuCl3·H2O in a 20% HCl aqueous solution to form a 0.1M concentration ruthenium salt solution.
7. The method for preparing a highly catalytic and long-durable titanium-based lead dioxide anode according to claim 1 or 2, characterized in that: In step 3, a dense PbO2 sublayer is firstly electrodeposited on the TiN / RuO2 composite intermediate layer, and a stainless steel plate of the same size as the anode is used as the cathode. In a solution containing Pb(NO3)2, HNO3 and [Emim]BF4, the current density is controlled to be 20-40 mA / cm 2 , a dense PbO2 sublayer is prepared by electrodeposition at a temperature of 60-80°C; then a porous PbO2 sublayer is anodic electrodeposited thereon, with a stainless steel plate of the same size as the cathode, in a deposition solution containing 0.2-0.6mol / L Pb(NO3)2, 0.1-0.2mol / L HNO3, 0.1-0.3mol / L CH3COONa·3H2O, 0.03-0.06mol / L Cu(NO3)2·3H2O and 0.01-0.03g / L sodium dodecylbenzene sulfonate, and the anodic deposition current density is controlled to be 100-200mA / cm 2 , deposited at a temperature of 50-80°C.
8. The method for preparing the highly catalytic and long-durable titanium-based lead dioxide anode according to claim 7, characterized in that: The multi-layer porous structure of the PbO2 catalytic surface is obtained by depositing dense PbO2 sublayers and porous PbO2 sublayers in sequence for multiple cycles. The fixed bottom of the PbO2 catalytic surface is always a dense PbO2 sublayer, and the outer surface is always a porous PbO2 sublayer. Each cycle is always composed of a dense PbO2 sublayer and a porous PbO2 sublayer thereon.
9. The method for preparing the highly catalytic and long-durable titanium-based lead dioxide anode according to claim 7, characterized in that: After the deposition is completed, the anode is rinsed with distilled water and dried at 60°C to obtain a multilayer porous PbO2 titanium anode.
10. The method for preparing the highly catalytic and long-durable titanium-based lead dioxide anode according to claim 7, characterized in that: The number of cycles of multi-periodic sequential deposition of the PbO2 catalytic surface layer of the multi-layer porous structure does not exceed 4.